Hours of Work - Tousignant, Fabienne (Relations industrielles / Industrial Relations, 1952)
The article reviews "Hours of Work," by William Goldner, edited by Irvin Bernstein, published by the Institute of Industrial Relations, University of California, Berkeley, 1952 (63 pages).